Structural basis for energy transfer in a huge diatom PSI-FCPI supercomplex - Xu, Caizhe; Pi, Xiong; Huang, Yawen; Han, Guangye; Chen, Xiaobo; Qin, Xiaochun; Huang, Guoqiang; Zhao, Songhao; Yang, Yanyan; Kuang, Tingyun; Wang, Wenda; Sui, Sen-Fang; et al. (Nature communications, 2020)
Diatom is an important group of marine algae and contributes to around 20% of the global photosynthetic carbon fixation. Photosystem I (PSI) of diatoms is associated with a large number of fucoxanthin-chlorophyll a / c proteins (FCPIs). We report the structure of PSI-FCPI from a diatom Chaetoceros gracili s at 2.38 Å resolution by single-particle cryo-electron microscopy. PSI-FCPI is a monomeric supercomplex consisting of 12 core and 24 antenna subunits (FCPIs), and 326 chlorophylls a , 34 chlorophylls c , 102 fucoxanthins, 35 diadinoxanthins, 18 β -carotenes and some electron transfer cofactors. Two subunits designated PsaR and PsaS were found in the core, whereas several subunits were lost. The large number of pigments constitute a unique and huge network ensuring efficient energy harvesting, transfer and dissipation. These results provide a firm structural basis for unraveling the mechanisms of light-energy harvesting, transfer and quenching in the diatom PSI-FCPI, and also important clues to evolutionary changes of PSI-LHCI. Diatoms are marine algae with an important role in global photosynthetic carbon fixation. Here, the authors present the 2.38 Å cryo-EM structure of photosystem I (PSI) in complex with its 24 fucoxanthin chlorophyll a/c -binding (FCPI) antenna proteins from the diatom Chaetoceros gracilis , which provides mechanistic insights into light-energy harvesting, transfer and quenching of the PSI-FCPI supercomplex.